2016
DOI: 10.1111/1365-2656.12558
|View full text |Cite
|
Sign up to set email alerts
|

Fitness costs of animal medication: antiparasitic plant chemicals reduce fitness of monarch butterfly hosts

Abstract: The emerging field of ecological immunology demonstrates that allocation by hosts to immune defence against parasites is constrained by the costs of those defences. However, the costs of non-immunological defences, which are important alternatives to canonical immune systems, are less well characterized. Estimating such costs is essential for our understanding of the ecology and evolution of alternative host defence strategies. Many animals have evolved medication behaviours, whereby they use antiparasitic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 67 publications
3
48
0
Order By: Relevance
“…While the exact mechanism by which cardenolides reduce parasite growth and virulence remains unclear, the current study provides a likely explanation for the observed increases in parasite tolerance of monarchs feeding on high-cardenolide milkweed (Sternberg et al, 2012;Tao et al, 2015Tao et al, , 2016. Butterflies fed on high-cardenolide milkweed have higher tolerance, meaning they suffer less fitness loss with increasing parasite spore loads than do monarchs reared on low-cardenolide milkweed.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…While the exact mechanism by which cardenolides reduce parasite growth and virulence remains unclear, the current study provides a likely explanation for the observed increases in parasite tolerance of monarchs feeding on high-cardenolide milkweed (Sternberg et al, 2012;Tao et al, 2015Tao et al, , 2016. Butterflies fed on high-cardenolide milkweed have higher tolerance, meaning they suffer less fitness loss with increasing parasite spore loads than do monarchs reared on low-cardenolide milkweed.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that infected monarchs reared on milkweeds with high cardenolide concentrations exhibit reduced parasite loads and increased tolerance to parasites (de Roode et al, 2008a(de Roode et al, , 2011aLef`evre et al, 2010;Sternberg et al, 2012;Gowler et al, 2015;Tao et al, 2015Tao et al, , 2016. Cardenolides may cause these reductions in parasite loads by increasing host immunity to the parasite, as has been seen in other systems (Lee et al, 2008;Povey et al, 2009;Simpson et al, 2015), or by direct inhibition of parasites (Cory and Hoover, 2006).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although caterpillars were never food limited in our study, AMF-mediated declines in plant biomass may have reduced caterpillar survival by decreasing the availability of young leaves because monarch caterpillars prefer younger leaves (Bingham and Agrawal, 2010). AMFmediated increases in foliar cardenolide concentrations did not correlate with declines in caterpillar survival in this study, although high cardenolide concentrations often reduce monarch caterpillar performance and survival (Zalucki et al, 2001a;Agrawal, 2005;Rasmann et al, 2009;Tao et al, 2016b).…”
Section: Amf Abundance Alters Specialist Herbivore Performance and Sumentioning
confidence: 55%
“…Monarch caterpillars, in contrast, have NA + /K + -ATPases that are insensitive to cardenolides (Dobler et al, 2012;Petschenka and Agrawal, 2015). Despite being able to tolerate cardenolides, both oleander aphids and monarch caterpillars exhibit reduced performance on host plants with high concentrations of cardenolides (Zalucki et al, 2001a;Agrawal, 2004Agrawal, , 2005Rasmann et al, 2009;de Roode et al, 2011;Colvin et al, 2013;Tao et al, 2016b;Birnbaum et al, 2017). Furthermore, both oleander aphids and monarch caterpillars sequester cardenolides (Rothschild et al, 1970;Malcolm and Brower, 1989;Malcolm, 1990;Züst and Agrawal, 2016b), providing an effective defense against aphid predators (Pasteels, 1978;Malcolm, 1989Malcolm, , 1992Pappas et al, 2007;Mooney et al, 2008) and monarch predators and parasites (Brower et al, 1968;Reichstein et al, 1968;Brower and Moffitt, 1974;Sternberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%